PENGARUH MEDIA FLASHCARD DALAM PRMBELAJARAN MENGENAL HURUF TERHADAP PERKEMBANGAN KOGNITIF BERPIKIR SIMBOLIK USIA 5-6 TAHUN - Yoga, Yoga; Syukri, M.; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the influence of flash card media on the cognitive development of symbolic thinking in children aged 5-6 years, before and after being given treatment using flash card media. This study used the one group pretest posttest design experimental method by collecting data through observation and documentation activities. The number of children in custody was 23 children, with 13 boys, 10 girls. Based on the data analysis carried out, significant results were found with an average value before being given treatment, namely 6.52 and an average value after being given treatment, namely 10.34. The results of the t-test calculation found that the value of t count t table was 10,650 1.7171. To find out how much influence flash card media has in learning to recognize letters on the cognitive development of symbolic thinking in children, an effect size test was carried out and it was found that, the test result was 2.21 1.00 which means that flash card media has an influence on the cognitive development of symbolic thinking in children aged 5-6 years in Cahaya Mentari PontianThis study aims to determine the influence of flash card media on the cognitive development of symbolic thinking in children aged 5-6 years, before and after being given treatment using flash card media. This study used the one group pretest posttest design experimental method by collecting data through observation and documentation activities. The number of children in custody was 23 children, with 13 boys, 10 girls. Based on the data analysis carried out, significant results were found with an average value before being given treatment, namely 6.52 and an average value after being given treatment, namely 10.34. The results of the t-test calculation found that the value of t count t table was 10,650 1.7171. To find out how much influence flash card media has in learning to recognize letters on the cognitive development of symbolic thinking in children, an effect size test was carried out and it was found that, the test result was 2.21 1.00 which means that flash card media has an influence on the cognitive development of symbolic thinking in children aged 5-6 years in Cahaya Mentari Pontianak Kindergarten. ak Kindergarten.